BREEDING OF HIGH-YIELDING AND HIGH-CHLOROPHYLL VARIETIES OF WINTER CHICKPEA (Modern education and development, 2024)
In the study, 20 winter chickpea genotypes were evaluated and selected under irrigated field conditions. Winter chickpea genotypes were determined by parameters such as growth period, plant height, location of lower pods relative to the soil surface, yield indicators, weight of 1000 grains, NDVI indicator, chlorophyll content, and protein content. Among the 20 studied varieties and lines of winter chickpea, 3-4 days earlier than standard varieties, adapted to mechanization, plant height 58.0-64.3 cm, weight of 1000 grains 345.6-370.1 g, yield 21.1-26 ,1 c/ha, protein content of 27.7-29.3 percent, high photosynthetic productivity, 7 genotypes were selected. In the study, the Obikor (KR20-CICTN-37) variety, which is early-yielding, adapted to mechanization, has high photosynthetic productivity, and is superior to standard varieties, was selected and recommended to be submitted to the Agricultural Crops Varieties Testing Center.